Pertanggung Jawaban Pidana Terhadap Pemberi dan Penerima Suap yang Dilakukan Oknum Pemerintah di Kabupaten Tabanan - I Kadek Faiza Putra Gunawan; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2024)
Acts of corruption often drag people who work in government agencies. KPK records show that corruption in the scope of agencies occurred in districts / cities as many as 409 problems in the period 2004-2020. the formulation of this research problem is: How is the Bribery Arrangement that occurs in the tabanan government. Criminal responsibility for the giver and receiver of bribes in the government environment in tabanan district discussing this problem, using Normative legal research. The regulation of bribery or every problem of corruption criminal activity must be processed by the court according to the existing provisions. Settlement is applied proactively based on existing laws and regulations and government authority. Each process of handling the problem must be carried out to check its progress. the Denpasar District Court's decision No. Case 16 //Pid. Sus-TPK//2020//PN, decided that the Defendant NI PUTU EKA WIRYASTUTI had been proven clearly and convincingly guilty of committing "the crime of corruption jointly and continuously".